Asset recovery in corruption cases: Comparative analysis identifies serious flaws in US tracing procedure. Issue 1 (4th January 2016) - Leasure, Peter
Abstract : Purpose: – Asset recovery proceedings increasingly target corrupt foreign officials who acquire lavish assets as a result of capital gained through criminal acts. One extremely difficult issue arising in asset recovery proceedings is whether the capital used to acquire the assets can be traced to a criminal act. The purpose of this paper is to critique US tracing procedure through comparative analysis. Design/methodology/approach: – A prominent series of cases brought by the USA and France against assets owned by Teodoro "Teodorín" Nguema Obiang, second Vice President of the Republic of Equatorial Guinea, produced mixed results on the tracing element. This paper utilizes a qualitative comparative case analysis to examine the US and French cases. Findings: – The US results reflect serious weaknesses in the US law as compared to more effective French asset recovery procedure. Originality/value: – Though this paper is certainly a comparative case study analysis, nearly identical facts and two different jurisdictions reaching separate conclusions bring us in the legal community as close as we can realistically come to quasi-experimental research. Comparative research in this area is severely lacking and sorely needed. The mechanisms identified in the French system clearly show flaws that are present in the US system.